Aflatoxin B1 Promotes Influenza Replication and Increases Virus Related Lung Damage via Activation of TLR4 Signaling - Sun, Yuhang; Su, Jiarui; Liu, Zixuan; Liu, Dandan; Gan, Fang; Chen, Xingxiang; Huang, Kehe (Frontiers in Immunology, 2018)
Aflatoxin B1 (AFB1) is one of the most common mycotoxins in feeds and food, regulating immune responses to mammals. Swine influenza virus (SIV) is a major pathogen of both animals and humans. However, few literatures were available about the relationship between AFB1 exposure and SIV replication. Here we for the first time investigated the involvement of AFB1 in SIV replication in vitro and in vivo, as well as its underlying mechanism using multiple cell line and mouse models. In vitro studies demonstrated that low concentration AFB1 (0.01 to 0.25 µg/ml) promoted markedly SIV replication as assessed by the increased viral titers, matrix protein (M) mRNA and nucleoprotein (NP) levels in MDCK, A549 and PAM cells. In vivo studies showed that 10 to 40 µg/kg of AFB1 exacerbated SIV infection and its severity in mice, characterized with the marked increases in viral M mRNA, NP, weight loss, lung index and damage. Further study showed that AFB1 up-regulated TLR4, but not other TLRs in SIV-infected PAMs and mice. AFB1 activated TLR4-NFκB signaling leading to TNF-α release as demonstrated by the increases in phosphorylated NF-κB 65 and TNF-α in PAMs and mice. To contrast, TLR4 knockdown or BAY 11-7082, a specific inhibitor of NF-κB, blocked the AFB1-promoted SIV replication and inflammatory responses in PAMs. Furthermore, TLR4 specific antagonist, TAK242, and TLR4 knockout attenuated the AFB1-promoted SIV replication, inflammation and lung damage in mice. We, therefore, conclude that AFB1 exposure aggravates SIV replication, inflammation and lung damage via activating TLR4-NF-κB signaling.